Perinatal Lead Exposure Alters Gut Microbiota Composition and Results in Sex-specific Bodyweight Increases in Adult Mice - Jianfeng Wu; Xiaoquan Wen; Christopher Faulk; Kevin F. Boehnke; Huapeng Zhang; Dana C. Dolinoy; Chuanwu Xi (2016)
Heavy metal pollution is a principle source of environmental contamination. Epidemiological and animal data suggest that early life lead (Pb) exposure results in critical effects on epigenetic gene regulation and child and adult weight trajectories. Using a mouse model of human-relevant exposure, we investigated the effects of perinatal Pb exposure on gut microbiota in adult mice, and the link between gut microbiota and bodyweight changes. Following Pb exposure during gestation and lactation via maternal drinking water, bodyweight in Avy strain wild-type non-agouti (a/a) offspring was tracked through adulthood. Gut microbiota of adult mice were characterized by deep DNA sequencing of bacterial 16S ribosomal RNA genes. Data analyses were stratified by sex and adjusted for litter effects. A Bayesian variable selection algorithm was used to analyze associations between bacterial operational taxonomic units and offspring adult bodyweight. Perinatal Pb exposure was associated with increased adult bodyweight in male (P < .05) but not in female offspring (P = .24). Cultivable aerobes decreased and anaerobes increased in Pb-exposed offspring (P < .005 and P < .05, respectively). Proportions of the 2 predominant phyla (Bacteroidetes and Firmicutes) shifted inversely with Pb exposure, and whole bacterial compositions were significantly different (analysis of molecular variance, P < .05) by Pb exposure without sex bias. In males, changes in gut microbiota were highly associated with adult bodyweight (P = .028; effect size = 2.59). Thus, perinatal Pb exposure results in altered adult gut microbiota regardless of sex, and these changes are highly correlated with increased bodyweight in males. Adult gut microbiota can be shaped by early exposures and may contribute to disease risks in a sex-specific manner.